NLRP1炎症体在糖尿病大鼠心肌组织内的表达 (Nan Fang Yi Ke Da Xue Xue Bao, 2020)
OBJECTIVE: To observe the expression of NLRP1 inflammasomes in myocardial tissues in rats with a high-fat and highsugar diet and in diabetic rats analyze the role of NLRP1 inflammasomes in the pathogenesis of diabetic cardiomyopathy. METHODS: Male SD rats were divided into normal control group, high-sugar and high-fat diet (HC) group and diabetes group. Rat models of diabetes were established by intraperitoneal injection of streptozotocin (STZ; 30 mg/kg). Serum levels of cholesterol (TC), triglyceride (TG), and fasting insulin (FINS) were measured after 8 weeks of feeding, and the insulin resistance index (IRI) and insulin sensitivity index (ISI) were calculated; Echocardiographic evaluation of cardiac structure and function was performed, and Western blotting and real-time fluorescent quantitative PCR (RT-qRCP) were used to detect the protein and mRNA expressions of NLRP1, ASC, and caspase 1 in the myocardial tissue. RESULTS: Compared with the control rats, the rats in the HC group had significantly increased body weight (BW), serum levels of TG and TC, mRNA expressions of NLRP1 and caspase 1, and the protein expression of NLRP1 (P < 0.01) without significant changes in FINS, IRI, ISI, or cardiac ultrasound findings (P > 0.05) or in myocardial ASC and caspase 1 protein expressions or serum levels of IL-1β and IL-18 (P > 0.05). In the diabetic rats, TC, TG, and FBG levels increased and FINS, ISI decreased significantly (P < 0.01); the left ventricular end-diastolic diameter (LVID) and the left ventricular end-systolic diameter (LVSD) increased while the ejection fraction (LVEF), short axis shortening rate (FS), and E/A ratio all decreased. The expressions of NLRP1/ASC/caspase 1 pathway mRNA and NLRP1 and caspase 1 proteins also increased but myocardium ASC protein expression did not show significant changes in the diabetic rats (P > 0.05). IL-1β and IL-18 levels were also significantly higher in the diabetic rats than in the control group (P < 0.05). Compared with those in HC group, the diabetic rats showed significantly increased serum FBG and decreased FINS, ISI and BW (P < 0.01) with decreased LVSD, LVEF and E/A ratio and increased levels of NLRP1 and caspase 1 protein expressions and serum L-1β and IL-18 levels (P < 0.01). CONCLUSION: Diabetes can cause abnormal changes in cardiac structure and functions and induce inflammatory response in the myocardium, which may be related to the activation of NLRP1/ASC/ caspase 1 inflammasomes.